EXPERIENCES OF CONDUCTING ONLINE EXAM PROCTORING IN LOW-RESOURCE SETTINGS: A SRI LANKAN CASE STUDY - Dilky N. Felsinger; Thilina Halloluwa; C. L. Ishani Fonseka (Інформаційні технології і засоби навчання)
Online tests are becoming increasingly common as online learning gains popularity. Online assessments are more prone to academic dishonesty than traditional exams. Ad hoc online proctoring techniques have been used by institutions to prevent academic misconduct during online tests. In contexts with unreliable infrastructure, such as slow internet connections and a lack of compatible equipment, it is challenging to figure out how to employ technology to proctor online tests swiftly and efficiently. The goal of this study was to gain a better understanding of the context and requirements for scaling up online exams in Sri Lanka as well as to investigate what options for improving the subsequent deployment of online proctoring systems in low-resource settings exist in order to maintain the caliber of academic programs. In this work, an in-class assignment for a Software Engineering course at a higher education institution in Sri Lanka was manually proctored using video conferencing software in a completely remote context. A post-exam feedback survey was used to collect information about participants' experiences with online proctoring. The survey was supposed to reveal the experiences about the devices used, internet connectivity, the factors that led to stress and perceptions about cheating during the exam. The data obtained from both the assignment and the survey was analyzed in order to make well-informed decisions about the future deployment of online proctoring technologies. This paper presents evidence of the experiment that strongly recommends that online exam proctoring solutions be developed after a careful examination of the constraints such as internet connection speed, stability, and affordability, as well as sudden power outages of the environment in which they will be utilised, in order to unlock the true potential of e-learning technologies.